Prospects of using zein markers in breeding waxy maize lines and varieties - V. V. Sidorova; Yu. A. Kerv; G. V. Matveeva; A. V. Konarev (Труды по прикладной ботанике, генетике и селекции)
Background. Among the numerous maize accessions in the VIR collection, Plant special attention is drawn to the lines and varieties of waxy maize due to their specific feature, that is, the content of high-quality grain starch that consists entirely of amylopectin. This amylopectin starch is of special interest to the medical, starch and syrup, and confectionary industries. One of the most important applications of amylopectin starch in medicine is its use as a component of "Volekam" blood plasma substitute. Besides amylopectin, the grain of other maize subspecies contains much amylose starch which makes production of purified amylopectin expensive. Therefore, the creation and study of domestic waxy maize lines and varieties is very topical, however it is insufficiently developed at present.Materials and methods. For the first time, zein electrophoresis was used to analyze waxy maize old landraces and breeding lines. Zein electrophoresis was carried out in vertical 10% PAA gels with 8 M urea. The solution for zein extraction contained 6 M urea and 0.01 M dithiothreitol. Results. The present research pursued the following aims: to use zein elecrophoretic patterns (protein markers) in screening waxy maize landraces and lines for their identification and fingerprinting; to determine the biotype composition of landraces and their polymorphism and degree of relationship; and to demonstrate the possibility of applying zein markers in the development of new waxy maize inbred lines by backcrossing the wx1 gene into the initial dent maize line.Conclusions. Zein electrophoretic patterns showed the uniqueness of each waxy maize accession. All the studied new lines are united by a decreased intensity of most zein pattern components, as well as by the presence of an intensive component 47 which is absent in the pattern of the initial lines of dent maize. Component 47 may serve as a protein marker for identifying waxy maize lines. All landraces were found to be composed of several biotypes (from two to five). Regardless of the intravarietal polymorphism, every variety has specific patterns which facilitate its identification.